Location-based pay at Google - Robson, Karen, (SAGE Business cases., 2021)
In August 2021 Google revealed that the company was considering applying a location-based pay scheme which could lead to employees who opt to work from home permanently experiencing a pay cut of up to 25%. The policy would apply to remote workers who lived in low-cost living areas. This case covers the proposed compensation policy and asks students to evaluate the pros and cons of the policy in order to understand whether this is a desirable policy for Google to implement.